China's expanding African relations : implications for U.S. national security - Thrall, Lloyd (Research report (Rand Corporation) ;, 2015)
"This report explores China's rapidly expanding involvement in Africa in order to better inform U.S. thinking about its relations both with China and with African states. The report pays particular attention to geostrategic competition in Africa, potential security threats, and opportunities on the continent. It examines the economic, political, and security interests driving Chinese engagement with African states and assesses potential medium-term changes in Sino-African relations across these three dimensions. It then assesses how China's interests and behavior on the continent affect the interests of the United States. In this matter, misperceptions often result from faulty assumptions about the potential for conflict over resources, images of Cold War-style geopolitical competition, and the nature of China's economic engagement with the continent. The report concludes by offering policy recommendations for U.S. and Army leaders concerned with U.S. security relationships with African states and with managing Sino-American relations in Africa. In particular, the report recommends that the United States should view China's sometimes-unfavorable activities in Africa in context and continue to seek opportunities to engage Beijing on mutual interests, such as defeating violent extremists, improving African infrastructure to promote trade and development, and encouraging economic and political stability on the continent."--Page 4 of cover